A salt-out strategy for purification of amphiphilic polymer-coated quantum dots. (7th September 2020) - Chen, Zhi-Liang; Lin, Yi; Zhu, Chun-Nan; Zhang, Zhi-Ling; Pang, Dai-Wen
Abstract : A purification strategy is presented that the OPA micelles are precipitated selectively in an OPA–QD solution by adding NaCl. Abstract : We developed a purification strategy for amphiphilic polymer-coated QDs via salting out. Dynamic light scattering (DLS) results revealed that the zeta potential of octylamine-grafted poly-(acrylic acid) (OPA) micelles is closer to zero than that of OPA-coated QDs and can be compressed to electric neutrality first after adding NaCl, inducing the selective precipitation of OPA micelles.